2020
DOI: 10.1007/s00259-020-04998-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumour blood flow for prediction of human prostate cancer aggressiveness: a study with Rubidium-82 PET, MRI and Na+/K+-ATPase-density

Abstract: Purpose Tumour blood flow (TBF) is a crucial determinant of cancer growth. Recently, we validated Rubidium-82 (82 Rb) positron emission tomography (PET) for TBF measurement in prostate cancer (PCa) and found TBF and cancer aggressiveness positively correlated. The aims of the present study were to determine the ability of TBF for separating significant from insignificant PCa and to examine the relation to underlying Na + /K +-ATPase density, which is relevant as 82 Rb is transported intracellularly via the Na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The coherency between quantitative TBF and PCa aggressiveness is being established, and the present results are in line with our previous publications [31,33]. However, the potential clinical role of quantitative TBF is undetermined in PCa management.…”
Section: Tumour Blood Flow For Prediction Of Pca Aggressivenesssupporting
confidence: 92%
See 2 more Smart Citations
“…The coherency between quantitative TBF and PCa aggressiveness is being established, and the present results are in line with our previous publications [31,33]. However, the potential clinical role of quantitative TBF is undetermined in PCa management.…”
Section: Tumour Blood Flow For Prediction Of Pca Aggressivenesssupporting
confidence: 92%
“…Across our previous studies [31][32][33], 43 patients underwent both pelvic [ 82 Rb]Rb PET/CT and clinical [ 68 Ga] Ga-PSMA-11 PET/CT and thereby met the inclusion criteria for the present study. All patients were recruited at the time of primary staging and hence none had previous therapy.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of 82 Rb as a Sodium-Potassium ATPase Pump Marker Rubidium-82 ( 82 Rb) has a similar biological pathway to that of a potassium ion (K + ). Once in the myocardium, it is taken up as a potassium analogue in the ion exchange pump (Na + /K + ATPase-pump) in cells [151]. Then, it is extracted proportional to blood flow: radioactivity is increased in viable myocardial cells, while the tracer is cleared rapidly from necrotic or infarcted tissue.…”
Section: Radioisotopic Imaging Of Perfusionmentioning
confidence: 99%
“…Jochumsen et al demonstrated increased uptake in higher grade prostate cancer compared to lower grade. 19 Like all blood-borne radiotracers, the tissue accumulation is governed both by perfusion and the abundance of the specific molecular target or binding mechanism. Which of these contributors dominates, and hence whether or not 82 Rb imaging can quantify Na + /K + -ATPase activity (either in cardiac or tumour imaging), remains to be fully determined.…”
Section: Introductionmentioning
confidence: 99%